IMPLEMENTASI ANALISIS DESAIN BERBASIS OBJEK PADA APLIKASI PEMINJAMAN SARANA DAN PRASARANA BERBASIS MOBILE - Nabila, Salma; Fitri, Anindo Saka; Pratiwi, Widya; Fahmi, Rohmat Ubaidillah; Zahran, Afif Ghani; Hilaly, Salwa Ghaliyah (Jurnal informasi dan komputer, 2023)
One of the activities that are often carried out is borrowing campus facilities and infrastructure, alsoexperienced by the academic community of the UPN "Veteran" East Java within areas of the Faculty ofComputer Science. However, this activity is considered inef ective and inef icient. Nevertheless, a solutionis needed to overcome this problem. By using the iconic method, the process starts from problemidentification, literature study, data collection (observation and interviews), needs analysis, and systemdesign in research. Producing an Information System as a solution, a solution application called "Apifak:Mobile-Based Facilities and Infrastructure Lending Application at the Faculty of Computer Science UPN"Veteran" East Java in the implementation of object-based design analysis. Apifak is a solution in theform of an application for the problem of inef ectiveness in an activity of borrowing facilities andinfrastructure. In supporting the Apifak application requires several steps that must be taken, includingcompiling flowchart, GUI, domain model, use case diagram, robustness diagram, sequence diagram, andclass diagram. This application is expected to increase ef ectiveness and ef iciency for users in lendingactivities.Keywords: Peminjaman, Sarana, Infrastructure, Technology, OOA